Survival and growth of hatchery and wild brown trout (Salmo trutta) parr in three Austrian headwater streams. Issue 1 (20th January 2017) - Pinter, Kurt; Weiss, Steven; Lautsch, Erwin; Unfer, Günther
Abstract: Brown trout populations of three headwater streams in the Northern Limestone Alps of Austria were supplemented by three‐month‐old hatchery‐reared parr from a wild and locally adapted strain and a nonresident domesticated hatchery strain. Growth and survival were monitored with three surveys over a period of 16 months after stocking. Fish descending from the wild reared origin strain demonstrated higher survival rates than the hatchery strain. Differences in growth were found among the investigated streams but not among the investigated strains. The differing temperature regimes of the streams were considered as the primary factor causing those disparities. We conclude that stocking measures had little or no additive effect on successful natural reproduction, as the resident wild brown trout performed significantly better than the stocked fish.